Refinement of the grain structure of additive manufactured titanium alloys via epitaxial recrystallization enabled by rapid heat treatment. (15th April 2020) - Zou, Zhiyi; Simonelli, Marco; Katrib, Juliano; Dimitrakis, Georgios; Hague, Richard
Abstract: The coarse prior-β grain structure in titanium alloys produced by additive manufacturing is associated to mechanical anisotropy and limited fatigue life. Here we report a novel methodology to refine such structure by rapid heat treatment of Ti–6Al–4V produced by laser powder-bed fusion. The refinement was analysed using high-temperature EBSD that showed, for the first time, how high angle boundary β grains nucleated and grew with quasi-equiaxed morphology by epitaxial recrystallization. These findings show the potential for such heating regime to be applied to control grain size, morphology and distribution in a wider category of structural alloys produced by additive manufacturing. Graphical abstract: Image, graphical abstract